Social work with looked after children 3rd revised edition - Cocker, Christine; Allain, Lucille (Transforming social work practice, 2018)
This revised edition details organisational systems and structures that are part of the assessment and planning process for looked after children. This is closely interwoven with discussions about their emotional development, educational, health and cultural needs and how these needs can be met through social work and a range of other services. The views of looked after children are highlighted through case studies and summaries of research findings, and the range of skills and knowledge necessary to support looked after children through the key events they experience, including loss, change and the development of new relationships, are explained and illustrated